Characterization of ZnO nanobelt-based gas sensor for H2, NO2, and hydrocarbon sensing - Abu Z. Sadek (2018)
A conductometric H2, NO2, and hydrocarbon gas sensor based on single-crystalline zinc oxide (ZnO) nanobelts has been developed. The nanobelt sensitive layer was deposited using a radio frequency (RF) magnetron sputterer. The microcharacterization study reveals that the nanobelts have a single crystal hexagonal structure with average thickness and width of about 10 and 50 nm, respectively. The sensor was exposed to H2, NO2and propene gases at operating temperatures between 150°C and 450°C. The study showed that optimum operating temperatures for the sensor are in the range of 300°C-400°C for H2, 300°C-350°C for NO2, and 350°C-420°C for propene sensing. © 2007 IEEE.